Measurement of Some Blood Parameters in Smokers of Men in the Province of Al-Muthanna - Areej Shakeer Jassum (Journal of Global Pharma Technology, 2018)
The detached of this study is to consider the influence of smoking on some blood parameters and to calculate the negative special influences of cigarette on the biochemical properties of blood in males. This study was lead at Al- Hussein Educational Hospital in AL- Muthanna province.